1991
DOI: 10.1152/jappl.1991.71.2.770
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of total respiratory impedance in infants by the forced oscillation technique

Abstract: The forced oscillation technique according to Làndsér et al. (J. Appl. Physiol. 41:101-106, 1976) was modified for use in infants. Adaptations, including a flexible tube to connect the infant to the measuring system and a bias flow to avoid rebreathing, did not influence impedance values. The linearity of the respiratory system was assessed and confirmed by 1) applying pseudo-random noise oscillations at three different amplitudes to 7 infants and 2) comparing in 12 infants impedance values obtained with pseud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 0 publications
2
26
0
Order By: Relevance
“…Recommendations have been developed by an American Thoracic Society/European Respiratory Society Working Party [115] and the specific preparation measures for the FOT and details of the methodology have been described by DESAGER et al [116]. The large values of Zrs in infants impose particularly strict performance requirements concerning the measurement set-up and the calibration procedure [117][118][119].…”
Section: Forced Oscillation Technique In Infancymentioning
confidence: 99%
“…Recommendations have been developed by an American Thoracic Society/European Respiratory Society Working Party [115] and the specific preparation measures for the FOT and details of the methodology have been described by DESAGER et al [116]. The large values of Zrs in infants impose particularly strict performance requirements concerning the measurement set-up and the calibration procedure [117][118][119].…”
Section: Forced Oscillation Technique In Infancymentioning
confidence: 99%
“…This is especially the case in young children or in adult populations where spirometry is not feasible, as the FOT does not require a learned manoeuvre [1][2][3][4][5].…”
mentioning
confidence: 99%
“…min -1 ). Previous studies have shown that the lower frequency ranges have proven very informative in adults [2, 17±19], children [20] and infants [6,8,15]. Furthermore, especially in preterm newborns the breathing pattern is often irregular and disturbed by various physiological occurrences (sighs, swallows, cardiac activities) and technical artefacts (drift, noise, air leaks) [21].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in newborns the lower cut-off frequency of the respiratory signals may be additionally increased. DESAGER et al [6] reported measuring problems of Zrs(jv) at low frequencies in infants due to spontaneous breathing. They found a high coefficient of variation and a low coherence at f <16 Hz.…”
Section: Discussionmentioning
confidence: 99%